Associations between sleep disturbance, treatment-related adverse events, and psychological distress in patients with breast cancer: a prospective cohort study - Yuqiu Li; Fang Zhao; Yanjun Zhou; Enfeng Fu; Shanshan Zhu; Lulu Yu; Hangcheng Xu; Qing Li; Qiao Li; Pin Zhang; Jiani Wang; Hongnan Mo (The Lancet Regional Health. Western Pacific)
Background: This study aimed to explore the relationship between sleep disturbance, treatment-related adverse events, and psychological distress in Chinese patients with breast cancer. Methods: This prospective cohort study reported on 300 female patients with breast cancer recruited from two medical centers across China between January 1, 2023, and October 31, 2023. Sleep disturbance and psychological health were assessed before and after every cycle of treatment using the Pittsburgh Sleep Quality Index (PSQI) and the Symptom Checklist-90 questionnaire (SCL-90). Statistical tests including t-test, Mann–Whitney U test, Spearman’s rank correlation analysis and multivariate linear regression analysis were used. The study was approved by the ethics committee of the National Cancer Center and written informed consent was obtained from each participant (22/272-3474). Findings: Patients were dichotomized into two groups: those with normal sleep (control; N=168) vs. those with sleep disorder (N=132). The incidence of most treatment-related adverse events such as nausea and vomiting (P=0.04), fatigue (P<0.001), numbness in the hands or feet (P=0.004), alopecia (P=0.02), memory deterioration (P=0.02), and photophobia (P=0.02) were significantly higher in the sleep disorder group at baseline compared to the normal sleep group. The baseline sleep quality of the patients was significantly correlated with the severity of adverse events (rs=0.16, P=0.007). Psychological health at baseline was also correlated with the adverse events score (rs=0.57, P<0.001). Multivariate analysis showed that psychological health was independently associated with the occurrence of adverse events (β=0.19, P <0.001). Besides, the pre-treatment total psychological health score in the baseline sleep disorder group was significantly higher than that in the normal sleep group (Z=-3.42, P=0.001). Furthermore, the severity of treatment-related adverse events (rs=0.32, P<0.001) and baseline sleep quality (rs=0.20, P=0.001) were respectively associated with psychological health. Interpretation: Poor baseline sleep quality is correlated with increased occurrence and severity of treatment-related adverse events in breast cancer patients. Besides, baseline psychological health is correlated with the occurrence of adverse events in breast cancer patients. Both baseline sleep quality and the severity of treatment-related adverse events significantly affect the psychological health of patients after treatment for breast cancer. We fill the knowledge gap and provide new insights for the factors affecting adverse events in breast cancer patients, which could reduce the incidence and severity of treatment-related adverse events and improve quality of life in patients with breast cancer. Our limitations are that we recorded only recent treatment-related adverse events instead of long-term effects and prognoses. Funding: This study was supported by the Nursing Cultivation Fund Project of the Key Discipline Fund of Internal Medicine from the Cancer Hospital of the Chinese Academy of Medical Sciences (grant no.: CICAMS-MONP2022001).